Investigation of wear behavior of Ti-6Al-4V/CNT composites reinforced with carbon nanotubes - GÜLLÜOĞLU, ARİF NİHAT; GÜLSOY, HAMİT ÖZKAN; BİLİCİ, MUSTAFA KEMAL (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2018)
In this study, the effects of different production conditions and different sintering conditions on microstructure, density and wear resistance of Multi-wall carbon nanotubes (CNTs) powders reinforced with Titanium (Ti-6Al-4V) powder by mechanical alloying were examined. The powders produced by mechanical alloying were compressed with a Cold Isostatic Press die under a pressure of 250 MPa in this molding machine to obtain cylindrical composite specimens. These raw specimens were extruded at 1275 degrees C for 60 minutes in a high purity argon atmosphere and high vacuum (1.2 10-5 mbar). The erosive wear behavior of the Ti-6Al-4V / CNTs metal matrix composite was studied using a pin-on-disc wear tester. The abrasion behavior of a Ti-6Al-4V / CNTs alloy after various heat treatments has been studied on abrasive wear. Under appropriate conditions it has been shown that reinforced CNTs can reduce the wear rate by more than two orders of magnitude. Various investigations have been carried out detailing the reinforcement rates of this improved wear performance. The friction and wear data show a clear surplus value added to the composite Ti-6Al-4V wear modes. As a result, in the experimental studies made, it is seen that the wear resistance increase according to the v/v % CNTs ratio which is directly supplemented to the volume. However, this properties had been decrease with the % 5 CNTs ratio.
Keywords: Carbon nanotubes; wear; sintering; TITANIUM-ALLOYS; ENHANCEMENT